2005
DOI: 10.1109/jstqe.2005.857385
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of tissue microstructures using a multimodal microscope design

Abstract: Abstract:We investigate a microscope design that offers high signal sensitivity and hyperspectral imaging capabilities and allows for implementation of various optical imaging approaches while its operational complexity is minimized. This system utilizes long working distance microscope objectives that enable for off-axis illumination of the tissue thereby allowing for excitation at any optical wavelength and nearly eliminating spectral noise from the optical elements. Preliminary studies using human and anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Recently, the use of hyperspectral (reflectance) imaging has gained interest in the analysis of microscopic structures, including microbes, tissues and associated constituents (Schultz et al , 2001; Demos et al , 2005; Demos, 2007; Haaland et al , 2007; Li et al , 2007). A review of recent literature has shown diverse application of short‐ and long‐wave microspectroscopy for the study of bacteria, cancer cells, human tissue morphology and general cellular structural analysis, but not for differentiating viable from non‐viable endospores.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of hyperspectral (reflectance) imaging has gained interest in the analysis of microscopic structures, including microbes, tissues and associated constituents (Schultz et al , 2001; Demos et al , 2005; Demos, 2007; Haaland et al , 2007; Li et al , 2007). A review of recent literature has shown diverse application of short‐ and long‐wave microspectroscopy for the study of bacteria, cancer cells, human tissue morphology and general cellular structural analysis, but not for differentiating viable from non‐viable endospores.…”
Section: Introductionmentioning
confidence: 99%
“…29 In brief, a compact diode-pumped solid-state laser operating at 266 nm (Intelite, Minden, NV) was used as the photoexcitation source to generate the AF images. The ex vivo images under 266-nm excitation were acquired using a 5 second exposure time with an approximate dose of 30 mJ∕cm 2 in order to optimize baseline image quality.…”
Section: Optical Imaging Protocolmentioning
confidence: 99%
“…Tissue was covered with a quartz slide and kept moist with phosphate buffered saline solution during imaging experiments. Ex vivo specimens were imaged without any tissue preparation using a prototype microscope-imaging platform detailed in a previous work 19 .…”
Section: Investigation Of the Origin Of Image Formation And Contrastmentioning
confidence: 99%